Dr. Carlos Henrique Camilo — Deep Plane Facelift — São Paulo - Henrique Camilo, Carlos (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Carlos Henrique Camilo, practicing in São Paulo, Brazil. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003414; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; brazil; são paulo